Impact of an oral nutritional supplement on improving body composition in older adults with malnutrition : A randomized controlled trial - Prasani Wickramawardhane; Chamila Dalpatadu; Andrew P Hills; Priyanga Ranasinghe; Ranil Jayawardena (World Nutrition Journal, 2023)
The consequences of malnutrition in the elderly often manifest as weight loss and altered body composition. The aim of this study was to assess the efficacy of an oral nutritional supplement (ONS) on body composition in malnourished older adults.